CE‐MS for metabolomics: Developments and applications in the period 2012–2014. Issue 1 (12th November 2014) - Ramautar, Rawi; Somsen, Govert W.; de Jong, Gerhardus J.; El Rassi, Ziad
<x xml:space="preserve">Abstract</x> In the field of metabolomics, CE‐MS is now regarded as a useful complementary analytical technique for the profiling of (highly) polar ionogenic metabolites in biological samples. Over the past few years, significant advancements have been made in CE‐MS approaches for metabolic profiling studies. This paper, which is a follow‐up of three previous review papers covering the years 2000–2012 [Electrophoresis 2009, 30, 276–291; Electrophoresis 2011, 32, 52–65; Electrophoresis 2013, 34, 86–98], provides an update of these developments covering the scientific literature from July 2012 to June 2014. Attention will be paid to novel interfacing techniques for coupling CE to MS and their implications for metabolomics studies. The potential of CEC‐MS and MEKC‐MS are also considered, and CE‐MS systems for high‐throughput metabolic profiling are discussed. The applicability of CE‐MS for metabolomics studies is demonstrated by representative examples in the fields of biomedical, clinical, microbial, plant, environmental, and food metabolomics. An overview of recent CE‐MS‐based metabolomics studies is given in a table, which provides information on sample type and pretreatment, capillary coatings, and MS detection mode. Finally, general conclusions and perspectives are given.